2019
DOI: 10.2116/analsci.19r005
|View full text |Cite
|
Sign up to set email alerts
|

Soft X-ray Absorption Spectroscopy of Liquids for Understanding Chemical Processes in Solution

Abstract: Soft X-ray absorption spectroscopy (XAS) involving excitation processes of a core electron to unoccupied states is an effective method to study local structures around excited C, N, and O atoms in liquid samples. Since soft X-rays are strongly absorbed by air and liquid itself, we have developed transmission-type liquid flow cells, where the absorbance of liquid samples can be easily reduced and optimized by controlling the liquid thickness. By using the transmission-mode XAS techniques, we have investigated l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 100 publications
0
14
0
Order By: Relevance
“…The XAS experiment was performed at the soft X-ray undulator beamline BL3U at the UVSOR-III Synchrotron . A detailed description of the liquid cell for XAS in transmission mode is available elsewhere. , The liquid cell was in an ambient pressure of helium gas, where a liquid layer was sandwiched between two SiC membranes with a thickness of 100 nm. Liquid samples were exchanged by using a tubing pump without changing the position of the liquid cell.…”
Section: Methodsmentioning
confidence: 99%
“…The XAS experiment was performed at the soft X-ray undulator beamline BL3U at the UVSOR-III Synchrotron . A detailed description of the liquid cell for XAS in transmission mode is available elsewhere. , The liquid cell was in an ambient pressure of helium gas, where a liquid layer was sandwiched between two SiC membranes with a thickness of 100 nm. Liquid samples were exchanged by using a tubing pump without changing the position of the liquid cell.…”
Section: Methodsmentioning
confidence: 99%
“…As described in the introduction, neutron scattering studies suggested the existence of pyridine clusters in the pyridine/water mixed solution, 31−33 and investigations based on soft X-ray absorption spectroscopy and quantum-chemical calculations hinted at the existence of the antiparallel π-stacked pyridine clusters in the solution. 34,35 As shown in Figures 5b−d, 6, S2, and S3, most of the stable (Pyd) 2 (H 2 O) n and (Pyd) 3 (H 2 O) n clusters contain the π-stacked (Pyd) 2 moiety. In these structures, H 2 O acts as an H-bonded bridge between the two pyridine monomers to form the π-stacked (Pyd) 2 , displaying the bands at 3480 and 3554 cm −1 characteristic for the doubledonor O−H stretching vibrations.…”
mentioning
confidence: 95%
“…While pyridine is soluble in water at any concentration, the structure of the pyridine/water solution is not fully understood. Extensive studies have been carried out for the pyridine/water solution using IR spectroscopy, Raman spectroscopy, neutron diffraction, and theoretical calculations. , Recent studies by neutron diffraction suggested that pyridine is not uniformly mixed with water, and domains in which an inhomogeneous pyridine/water mixture forms occur locally. Kosugi and co-workers applied soft X-ray absorption spectroscopy to pyridine/water solutions and proposed that π-stacked antiparallel pyridine clusters are dominant under pyridine-rich conditions; they also demonstrated that such clusters occur even in very dilute solutions. , In this sense, the knowledge of the structures and the vibrational spectra of the (Pyd) m (H 2 O) n clusters can be quite useful for the analysis of the local structure in a pyridine/water mixed solution. In the current study, we measure the IR spectra in the O–H stretching region for various (Pyd) m (H 2 O) n clusters and determine the corresponding molecular structures with the aid of quantum-chemical calculations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several groups measured XAS of liquid samples in transmission mode by packing liquid samples with Si 3 N 4 membranes (Nä slund et al, 2005;Schreck et al, 2011;Meibohm et al, 2014;Sellberg et al, 2014). We have also developed a transmission-type liquid flow cell for XAS of liquid samples (Nagasaka et al, 2020a). The liquid layer is sandwiched between two Si 3 N 4 membranes and the liquid thickness is controllable from 2000 nm to 20 nm by controlling the helium pressure around the liquid cell from 0.1 MPa to 0.12 MPa (Nagasaka et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%